Unveiling the nexus between irradiation and phase reconstruction in tin-lead perovskite solar cells - Wenbo Li; Zhe Li; Shun Zhou; Yanzhuo Gou; Guang Li; Jinghao Li; Cheng Wang; Yan Zeng; Jiakai Yan; Yan Li; Wei Dai; Yaoguang Rong; et al. (Nature Communications)
Abstract Tin-lead perovskites provide an ideal bandgap for narrow-bandgap perovskites in all-perovskite tandem solar cells, fundamentally improving power conversion efficiency. However, light-induced degradation in ambient air is a major issue that can hinder the long-term operational stability of these devices. Understanding the specifics of what occurs during this pathway provides the direction for improving device stability. In this study, we investigate the long-term stability problem of tin-lead perovskites under irradiation, counterintuitively discovering an irreversible phase reconstruction process. In-situ photoluminescence spectroscopy is used to monitor the reconstruction process, which involves the reaction of oxygen with photoexcited electrons to form superoxide. It is proposed that Pb-rich regions appear on the surface after Sn2+ oxidation, and these Pb-rich regions are reconstituted from the yellow phase of formamidinium lead iodide to the black phase with prolonged irradiation. This study highlights the phase reconstruction process during the degradation of tin-lead perovskites, providing valuable insights into the superoxide degradation mechanism and guiding further stability improvements for narrow-bandgap tin-lead perovskites and tandem solar cells.